2017
DOI: 10.1515/ijhp-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of assessments for procedural skills in physiotherapy education / Assessment von prozeduralen Fähigkeiten in der physiotherapeutischen Ausbildung: Ein systematischer Review

Abstract: Introduction: Learning of procedural skills is important in the education of physiotherapists. It is the aim of physiotherapy degree programmes that graduates are able to practice selected procedures safely and efficiently. Procedural competency is threatened by an increasing and diverse amount of procedures that are incorporated in university curricula. As a consequence, less time is available for the learning of each specific procedure. Incorrectly performed procedures in physiotherapy might be ineffective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Practical techniques tend to be sequential and predictable, so the structure of a checklist allows for a detailed and objective assessment of compliance with the sequence of steps [ 33 ]. In a systematic review, it was concluded that further development of valid and reliable instruments for the evaluation of practical skills is needed in physiotherapy [ 34 ]; hence, in the absence of “gold standard” instruments, we developed custom measures that proved to be fit for purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical techniques tend to be sequential and predictable, so the structure of a checklist allows for a detailed and objective assessment of compliance with the sequence of steps [ 33 ]. In a systematic review, it was concluded that further development of valid and reliable instruments for the evaluation of practical skills is needed in physiotherapy [ 34 ]; hence, in the absence of “gold standard” instruments, we developed custom measures that proved to be fit for purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Rubrics such as OSATS (Objective Structured Assessment of Technical Skills) have been reported in structured medical-surgical procedures with satisfactory results [ 30 , 35 ]. Rubrics make it possible to determine the skills necessary to carry out a procedure using satisfaction scales [ 34 ]. In our study, the decision to use two instruments was made because, although the checklist is widely used in the literature, it cannot accurately distinguish the level of quality of the student’s practical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the study of the acquisition of procedural skills was primarily in the field of medical and especially surgical education. However, other health professions such as nursing and physiotherapy education have developed assessment and teaching approaches for these skills as well (Oermann, Muckler & Morgan, 2016;Sattelmayer, Hilfiker & Baer, 2017). Defining procedural skills is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the study of the acquisition of procedural skills was primarily in the field of medical and especially surgical education. However, other health professions such as nursing and physiotherapy education have developed assessment and teaching approaches for these skills as well (Oermann et al 2016;Sattelmayer et al 2017). Defining procedural skills is challenging.…”
Section: Introductionmentioning
confidence: 99%